Estimating commute-travel implications of telecommuting by female employees in Kuala Lumpur, Malaysia - M.Jaff, Mootaz; Kadar Hamsa, Abdul Azeez (Elsevier, 2018)
A number of Malaysian cities are experiencing severe traffic congestion resulting from rapidly increasing vehicle ownership and usage, and the insufficient supply and inferior quality of public transport. The trend of congestion, frequent traffic accidents and air pollution is nowhere more prevalent in Kuala Lumpur where telecommuting is increasingly being perceived as a viable travel demand management strategy. Due to a number of unique travel characteristics of female commuters and the relatively large participation rate of women in the Malaysian work force, telecommuting by female employees seems a more relevant and potentially more crucial means of alleviating rush hour traffic in the Kuala Lumpur metropolitan area. The aim of this study is to estimate both the potential and actual travel implications of telecommuting by female employees. Therefore, this study is exploratory in nature as it mainly aims to explore the influence of the propagation of a phenomenon (i.e., telecommuting among female employees in Kuala Lumpur) on travel demand, and is thus mainly a quantitative research. The travel implications estimated in this paper include the reduction in commute trips, with a particular emphasis on the reduction in single occupancy vehicles (SOVs) entering the city of Kuala Lumpur during peak hours; vehicle and passenger-kilometers forgone; and time savings as a result of the elimination of the daily commute. The findings clearly show the potential of substantial reduction in vehicle and passenger-kilometers travelled, as well as potential time savings of more than 7000 employee-hours/day under an optimal adoption scenario. Furthermore, telecommuting by female employees could potentially result in a daily reduction of up to7.8% of all SOVs entering Kuala Lumpur in 2019; however, there is a large gap between that potential reduction and the maximum actual reduction of 0.96%.